Implementation of the Gamification Method for Employee Training Systems at PT XYZ Using the Moodle Learning Management System (Jurnal Infra, 2026)
This study aims to develop a Moodle-based Learning Management System (LMS) to address employee training challenges at PT XYZ. The main obstacle faced by the company is the onboarding process, which was previously conducted manually via WhatsApp, resulting in unstructured materials and difficult monitoring. Therefore, this system is designed to provide modular learning paths, automated evaluation mechanisms, and data-based progress tracking features to improve training management. As a primary solution to enhance user engagement, this study applies gamification methods that include points (XP), levels, activity badges, and leaderboards. Its technical implementation is supported by the development of an additional plugin named "My Command Center," which functions to manage automatic badge assignment based on learning activity completion. This approach aims to transform the monotonous training process into a more interactive and motivating learning experience. Testing results indicate that the system operates stably without major errors and is able to significantly accelerate the onboarding process duration. Evaluation using User Acceptance Testing (UAT) proves that gamification integration effectively increases employee motivation, comprehension, and engagement, as evidenced by improved module completion rates, XP accumulation, and assessment results. Thus, the application of gamification within the LMS is proven to be an effective solution for enhancing training quality and efficiency at PT XYZ.